Strength training promotes attenuation of fatty liver while improving insulin resistance and inflammatory biomarkers in obese rats induced by high-fat diet - S. Torezani-Sales; A.P.L. Damiani; A.R. Madureira; J.P. Cordeiro; G.H. Taufner; B.V. Nogueira; M.C. Dias; M.M. Sugizaki; A.S. Leopoldo; A.P. Lima-Leopoldo (Brazilian Journal of Medical and Biological Research)
Obesity is an independent risk factor for metabolic dysfunction-associated steatotic liver disease (MASLD). Non-pharmacological strategies, such as strength training (ST), have been investigated for their effectiveness in attenuating MASLD. This study evaluated the effects of ST on hepatic fat accumulation in an experimental model of obesity. Thirty-day-old male Wistar rats (∼150 g) were assigned to either a standard diet (SD) or a high-fat diet (HFD). The experimental protocol lasted 26 weeks and was divided into two phases: 1) obesity induction and maintenance (16 weeks) and 2) ST intervention (10 weeks). After the 16th week, HFD-fed rats were further divided into sedentary obese (Ob) and obese trained (ObST) groups. The ST protocol consisted of 4-5 vertical ladder climbs with 60-s intervals, three times per week, using 50-100% of maximal load. Body weight (BW), fat pads, total body fat (BF), adiposity index (AI), and muscle strength were assessed, as were glycemic, lipid, inflammatory, and histological parameters. ST reduced BW, epididymal and visceral fat depots, triglycerides, total cholesterol, glucose, leptin, and tumor necrosis factor (TNF)-α levels while improving insulin resistance. In conclusion, ST significantly attenuated hepatic steatosis in obesity, promoting metabolic and anti-inflammatory benefits. These findings suggest that ST may be an effective therapeutic strategy for MASLD, and further studies are needed to elucidate its molecular mechanisms and clinical applications.